MicroRNAs in bone metastases: mechanisms and research progression - He, Wei; Wang, Zhen; Li, ZiHan (Frontiers in Oncology, 2025)
Bone metastasis, an exceedingly critical and often life - threatening complication in the course of diverse cancer progression, impacts nearly all tumor types, with an especially pronounced prevalence in breast, prostate, lung, liver, and thyroid malignancies. These metastatic lesions are typically localized in the spine, pelvis, shoulders, and distal femur, thereby exerting a substantial influence on patients’ quality of life and prognosis. In numerous instances, the early detection of cancers frequently coincides with patients presenting symptoms induced by bone metastases, which strikingly highlights the severe and debilitating nature of this condition. MicroRNAs (miRNAs), a class of short non - coding RNAs, have emerged as pivotal regulators of gene expression. They are widely and comprehensively acknowledged for their indispensable role in cancer initiation, progression, invasion, and metastasis. Abundant evidence has underscored the involvement of specific miRNAs at various stages of bone metastasis, further emphasizing their vital contribution to the pathogenesis of metastatic bone disease. In this comprehensive review, we systematically collate and summarize the current state - of - the - art knowledge regarding the participation of miRNAs in bone metastasis within breast, prostate, lung, liver, and thyroid cancers. Moreover, we thoroughly explore the potential of miRNAs as therapeutic targets or advanced - generation therapeutic agents for bone metastasis. Concurrently, we also in - depth investigate their function as predictive biomarkers for earlier diagnosis and the development of optimized treatment strategies for cancer patients.